Excessive Dietary Lipid Affecting Growth Performance, Feed Utilization, Lipid Deposition, and Hepatopancreas Lipometabolism of Large-Sized Common Carp (Cyprinus carpio) - Fan, Ze; Li, Jinnan; Zhang, Yuanyuan; Wu, Di; Zheng, Xianhu; Wang, Chang'an; Wang, Liansheng (Frontiers in Nutrition, 2021)
With the aim to optimize the dietary lipid requirement of large-size common carp (C. carpio) and further strengthen the precise nutrition regulation in the breeding process of common carp (Cyprinus carpio), an 82-day study was conducted to assess the dietary lipid requirement for large-size common carp (Cyprinus carpio). Six isonitrogenous (300 g/kg protein) pelletized diets with different dietary lipid levels (30, 60, 90, 120, 150 and 180 g/kg) were fed to triplicate fish groups with 75 individuals (with initial mean weight of 247.00±16.67 g). Results showed that weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER) significantly increased as dietary lipid level increased from 30 to 60 g/kg (P<0.05) and then declined. A significantly lower feed conversion rate (FCR) was observed in 60 g/kg lipid treatments (P<0.05). Significantly higher muscle crude protein contents were obtained in 60 and 90 g/kg treatments (P<0.05). Crude lipid content of hepatopancreas significantly increased with increasing dietary lipid (P<0.05). The expression of lipoprotein lipas (LPL) and carnitine palmitoyl transferase-1 (CPT1) in hepatopancreas significantly downregulated with increasing dietary lipid, while the expression of growth hormone (GH) and insulin-like growth factor-1 (IGF-1), fatty acid synthetase (FAS), acetyl-CoA Carboxylase-1(ACC-1) and sterol regulatory element binding protein (SREBP) upregulated first in 30 and 60 g/kg lipid treatments and then downregulated significantly in other treatments. Based on the second-order polynomial regression analysis of the WGR and FCR, dietary lipid requirements for large-size common carp are, respectively, 59.5 and 70.4 g/kg.